The The Degree to Which Third-Grade Learners Mathematical Problem-Solving Skills "A Field Study in Lattakia City": The Degree to Which Third-Grade Learners Mathematical Problem-Solving Skills "A Field Study in Lattakia City" (Journal of Hama University, 2025)
The aim of the current research is to determine the degree to which third-grade learners possess mathematical problem-solving skills. The research sample consisted of (320) learners. The researcher used the descriptive approach, and a test of mathematical problem-solving skills was designed, consisting of six skills: (the skill of understanding the problem, the skill Problem analysis, the skill of developing a plan, the skill of verification, the skill of implementation, and the skill of presentation). The total score for the test was (80) points. The validity of the test was confirmed by presenting it to a group of arbitrators, and the reliability was confirmed by applying the test to a survey sample, and calculating the reliability coefficient, which reached a value of (0.93)       The results of the research showed that the third grade learners possessed mathematical problem-solving skills in mathematics to a moderate degree, and that their possession of the skill of understanding the problem came to a high degree, and that their possession of the two skills (analyzing the problem and developing a plan) came to a middle degree, while the learners’ possession of the skills of (implementation,  verification, and presentation) came in at a low degree, and the results also showed that there was no statistically significant difference between the average scores of the research sample members on presentation skill according to the gender variable.      The researcher recommended a number of proposals, the most important of which were conducting a study of the role of teachers in developing mathematical problem-solving skills among learners in the basic education stage, and conducting an analytical study of mathematics books in the basic education stage. To see the extent to which problem-solving skills are included
Keywords: Mathematical Problem-solving skills, Third-Grade Learners.